CD8+ Tregs revisited: A heterogeneous population with different phenotypes and properties - Niederlova, Veronika; Tsyklauri, Oksana; Chadimova, Tereza; Stepanek, Ondrej (European journal of immunology, 2021)
Regulatory T cells (Tregs) play a key role in the peripheral self-tolerance and preventing autoimmunity. While classical CD4+ Foxp3+ Tregs are well established, their CD8+ counterparts are still controversial in many aspects including their phenotypic identity and their mechanisms of suppression. Because of these controversies and because of only a limited number of studies documenting the immunoregulatory function of CD8+ Tregs in vivo, the concept of CD8+ Tregs is still not unanimously accepted. We propose that any T-cell subset considered as true regulatory must be distinguishable from other cell types and must suppress in vivo immune responses via a known mechanism. In this article, we revisit the concept of CD8+ Tregs by focusing on the characterization of individual CD8+ T-cell subsets with proposed regulatory capacity separately. Therefore, we review the phenotype and function of CD8+ FOXP3+ T cells, CD8+ CD122+ T cells, CD8+ CD28low/- T cells, CD8+ CD45RClow T cells, T cells expressing CD8αα homodimer and Qa-1-restricted CD8+ T cells to show whether there is sufficient evidence to establish these subsets as bona fide Tregs. Based on the intrinsic ability of CD8+ Treg subsets to promote immune tolerance in animal models, we elaborate on their potential use in clinics.
Keywords: antigeny CD28; Immune Tolerance; zvířata; lidé; Regulatory T cells; T-Lymphocytes, Regulatory; CD28 Antigens; fenotyp; Phenotype; Homeostasis; imunologická tolerance; Autoimmunity; Tolerance; CD8-Positive T-Lymphocytes; T-lymfocyty - podskupiny; Humans; regulační T-lymfocyty; Animals; CD8 T cells; CD8-pozitivní T-lymfocyty; T-Lymphocyte Subsets